Evaluation of Bubaline Derived Composite Collagen Glue for Enhanced Healing and Cosmetic Efficacy of Aural Haematoma in Dogs - Sharma, Deepshikha; Prakash Shukla, Bramha; Jain, Reshma; Pathak, Rekha; Shukla, Supriya; Deewan Singh Raghuvanshi, Pawan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The objective of the present study was to evaluate collagen glue for the treatment of aural haematoma in dogs. Eighteen clinical cases of dogs suffering from aural haematoma were divided into three groups. In group I (n=6), horizontal mattress sutures were applied, in group II (n=6) horizontal mattress sutures along with collagen glue was applied and in group III (n=6) sole application of collagen glue was done for the obliteration of dead space. The cosmetic appearance of ear pinna was compared in all the groups after complete healing. Haemato-biochemical parameters recorded revealed that the most values were within normal physiological limits without group or period effect, except for total leukocyte count and neutrophils (%) which significantly significant in all groups from day 0 to day 7 post-treatment and the values were also lower in group III than group I. Histological observations concluded that collagen glue treated group showed reduced inflammatory cells, fast proliferation of fibroblasts, early epithelialization and improved neovascularization along with significant collagen deposition and arrangement.